Lingguizhugan Decoction Protects against High-Fat-Diet-Induced Nonalcoholic Fatty Liver Disease by Alleviating Oxidative Stress and Activating Cholesterol Secretion - Lili Yang; Weili Lin; Colleen A. Nugent; Shijun Hao; Haiyan Song; Tao Liu; Peiyong Zheng (International Journal of Genomics)
Background. Nonalcoholic fatty liver disease (NAFLD) has become a leading cause of liver transplantation. Lingguizhugan decoction (LGZG), a classical Chinese herbal formula, has beneficial effects on NAFLD animal models. Our study examined the impact of LGZG on hepatic global transcriptome of high-fat-diet-induced NAFLD rats. Methods. Three groups of Wistar rats were included: normal, NAFLD model, and LGZG-treated NAFLD groups. Four weeks for the treatment, liver tissues were harvested for RNA sequencing. Differentially expressed genes (DEGs) and enriched pathways were detected on hepatic global transcriptome profile. Real-time PCR validated the regulatory patterns of LGZG on NAFLD rats. Results. DEGs between the NAFLD model and normal groups indicated the elevated peroxisome proliferator-activated receptor (PPAR) and hedgehog signaling pathways in NAFLD rats. In bile secretion pathway, genes involved in cholesterol secretion were activated by LGZG treatment. Increased expression of antioxidant OSIGN1 and decreased expression of genes (AHR, IRF2BP2, and RASGEF1B) that induce oxidative stress and inflammation were observed in NAFLD rats treated with LGZG. The regulatory patterns of LGZG treatment on these oxidative stress-related genes were confirmed by real-time PCR. Conclusion. Our study revealed a “two-hits-targeting” mechanism of LGZG in the treatment for NAFLD: alleviating oxidative stress and activating cholesterol secretion.